Figure drawing in proportion easy to remember, accurate anatomy for artists - Massen, Michael (Cincinnati, Ohio North Light Books, 2016)
An easier way for drawing people in proportion using internal and comparative measurements.
Drawing basics -- Anatomy basics -- The body's internal proportions -- The body's comparative proportions -- Figure demonstrations.
Includes index.
Prof. Jocelyn C. Pinzon (Recommending faculty) - Bookfair2017
Keywords: Figure drawing -- Technique; Anatomy, Artistic; Anatomy, Artistic; Figure drawing -- Technique